Effects of Cooking Medium and Batter Formulation on Quality Attributes Of Fried Fish Fillets - Moradi, Yazdan (2008)
Fried breaded fish fillets are consumed for their unique flavor and textural characteristics which are contributed by the preparation and the breading process. However, the cooking process can cause detrimental changes to the highly valued lipid characteristics of the fish lipid. Therefore, this study was carried out with the objectives of evaluating the changes that could be brought upon by the presence of breading materials, preparation process (pre-frying and pre-drying) and the cooking methods on the desired quality attributes of the breaded fish fillets. The effects of resistant starches on the quality attributes of the breaded fillets were also evaluated. The breaded and non-breaded black pomfret (Parastromateus niger) fillets were deep-fried in sunflower oil and palm olein and evaluated for the physico-chemical properties such as fat content, moisture loss, texture and color changes. The frying process significantly (P<0.05) changed the fat and moisture content in the fillets. The presence of breading materials decreased significantly (P<0.05) the moisture loss and the fat uptake. However, the lipid compositions were observed to change significantly. The n-3/n-6 ratios were decreased in all fried samples. The palm olein fried samples had significantly (P<0.05) higher n-3/n-6 ratio than the sunflower oil fried samples. Breaded fillets were also pre-fried prior to frozen storage to evaluate the effect of pre-frying on the lipid profile of the samples. The pre-frying treatments resulted in the decrease of the saturated fatty acids concentration and an increase of the monounsaturated fatty acids for all samples. The polyunsaturated fatty acids content was found to increase in the sunflower oil fried samples and decreased in the palm olein fried ones. The effects of three final cooking methods on the quality attributes of breaded fillets were also determined. Among the three methods, oven cooking had the least changes in the parameters evaluated. The concentration of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the oven cooked samples was about two times higher than the samples cooked by other methods. Oven cooking methods also showed lower thermal oxidation and higher n-3/n-6 ratio than the other two cooking methods. The highest and lowest values of hardness in the final product were observed for those fried and microwaved, respectively. Pre-drying before frying of breaded fillets affected the moisture content, the fat content and the hardness of the final product significantly (P<0.05). A positive correlation (r = 0.90) between the pre-drying time and moisture content, and between pre-drying time and hardness (r = 0.96), and a negative correlation between the pre-drying time and the fat uptake (r = -0.78) were found. The incorporation of the resistant starches in the batter formulation affected all trends of moisture and fat migration in and out of the breading materials. The moisture content increased while the fat content decreased significantly (P<0.05) in all breaded samples containing resistant starches as compared to the control. A significant (P<0.05) increase in hardness and crispiness of the samples containing resistant starches were also observed.